Pengenalan Kosa Kata dan Tata Bahasa Inggris Dengan Menggunakan Grammar Translation Method Kelas VII SMP Negeri Gudang Arang - Marnina Marnina; Angla F Sauhenda (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The implementation of this community service activity was carried out in class VII SMP Negeri Gudang Arang Merauke with a total of 20 participants. It is hoped that these students can understand and know English as a foreign language and as an effort to increase interest, motivation, will, and interest. Students in learning English in the field of education. This service contributes to learning English, especially for beginners (Young Learners) as an effort to increase students’ interest in learning English. In addition, this activity contributes to realizing education in Junior High School (SMP) to foster students’ interests and talents and motivation in learning English and as an effort to provide an introduction to English for the beginner level (Young Learners). This service is carried out in the form of a workshop which includes socialization in the form of training/introduction and mentoring. The material for the service activities is divided into two, namely exposure to motivational material interest in learning English and introduction to English vocabulary and grammar to be able to read texts in English. The expected goals of this service are: 1) increasing students’ knowledge and understanding of how to learn English is easy; 2) increasing students’ skills in English and students being able to understand reading material well. From the whole series of community service activities, the main hope is an improvement. Improving conditions from not knowing, not understanding to very understanding, and from low be high in terms of interest, motivation, willingnesss and interest of sudents in learning English especially English vocabulary and grammar